2003
DOI: 10.1093/hmg/ddg255
|View full text |Cite
|
Sign up to set email alerts
|

A novel genetic variant in the apolipoprotein A5 gene is associated with hypertriglyceridemia

Abstract: The apolipoprotein A5 gene (APOA5 ) has been shown to play an important role in determining plasma triglyceride concentrations in humans. We describe here a novel variant, c.553G>T, in the apolipoprotein A5 gene that is associated with hypertriglyceridemia. In contrast to some other polymorphisms, which occur in non-coding regions of the gene, this variant occurs within the coding region and causes the change of amino acid sequence (a substitution of a cysteine for a glycine residue). The minor allele frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
136
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(155 citation statements)
references
References 30 publications
16
136
0
3
Order By: Relevance
“…According to our WES findings, APOA5 C553G T (rs2075291) is a causative gene mutation. Additionally, in agreement with the findings of a previous report 40) , the prevalence of the TT genotype (rs2075291) is high in affected Taiwanese populations. According to the ExAC browser (http://exac.broadinstitute.org/), which contains exome sequence data for 61,486 individuals as a global "reference set," there are 26 individuals with homozygous mutations with rs2075291 (allele frequency: 0.00637).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…According to our WES findings, APOA5 C553G T (rs2075291) is a causative gene mutation. Additionally, in agreement with the findings of a previous report 40) , the prevalence of the TT genotype (rs2075291) is high in affected Taiwanese populations. According to the ExAC browser (http://exac.broadinstitute.org/), which contains exome sequence data for 61,486 individuals as a global "reference set," there are 26 individuals with homozygous mutations with rs2075291 (allele frequency: 0.00637).…”
Section: Discussionsupporting
confidence: 92%
“…In Taiwan, two haplotypes of APOA5 (rs662799 and rs2075291) have been found to be closely related to HTG 39) . Moreover, the TT genotype of rs2075291 in the Taiwanese population was reported to be associated with HTG by Kao J. et al In that report, the frequency of the TT genotype of rs2075291 was reported to be 8.7% in the HTG group 40) . Based on these previous studies, SNP rs2075291 (553G T) is closely associated with HTG.…”
Section: Discussionmentioning
confidence: 92%
“…Another SNP, rs2075291 (553G4T), has also shown to be associated with elevated triglycerides in some Asian studies. [36][37][38][39][40][41] This SNP has a MAF of 2% in the HapMap Han Chinese population and 3.8% in Hong Kong Chinese without hyperlipidaemia. 41 The strong association of rs662799 with plasma triglycerides could not be due to rs2075291 in the Hong Kong Chinese population as the two SNPs are not in strong LD (r 2 ¼0.13) and the effect of rs2075291 on triglycerides in familial combined hyperlipidaemia is much weaker than that of rs662799.…”
Section: Discussionmentioning
confidence: 99%
“…DNA from patients and control subjects was extracted using the "G-spin™ Total DNA Extraction Kit" (iNtRON Biotechnology, Inc, South Korea). According to previous published protocols (Table 1), SNPs in APOA5 were genotyped by polymerase chain reaction and restriction fragment length polymorphism (PCR-RFLP) using the "Maxine PCR PreMixKit" (iNtRON Biotechnology, Inc, South Korea) [18,19].…”
Section: Genotyping Of Snpsmentioning
confidence: 99%